Carlos Walter Porto-Gonçalves. The Amazon and the construction of a decolonial methodological horizon of geographical practice - CRUZ, Valter (Utopía y Praxis Latinoamericana, 2024)
The objective of this article is to analyze how, based on his studies on the Amazon, Carlos Walter Porto-Gonçalves constructed a thematic-empirical reading of the region and, at the same time, an original methodological horizon of geographical practice. Our working hypothesis is that the research experience with the Amazon gave the author rules and compasses to build a renewal in Brazilian Geography. We propose to dialogue with the author's work by systematizing the epistemological gestures and analytical clues that, articulated, constitute a renewed horizon of decolonial reading of the geographical nature of the social, and that will be presented throughout this text in the format of: a) two epistemological gestures, two fundamental forms of problematization of the relationship with knowledge about and from the Amazon: i) combat Eurocentrism and the colonial invention of the Amazon, and, ii) learning with Amazonian horizons - the Amazon as the center of world; b) five analytical clues that point to the construction of an original conception of geography that, at the same time, affirm and stress the tradition of the discipline: i) the Amazon as an unequal accumulation of times: ii) the political ecology of the society-society relationship nature in the Amazon; iii) Geography as a verb: a look at the Amazon from those below and from r-existences; iv) territorial tensions: the conflict as a key to reading the Amazon; v) the struggles for life, for dignity and for territory in the Amazon.